Analisis Bibliometrik Layanan Konseling dengan Teknik EFT dalam Mengatasi Kecemasan Sosial - Oktafiani, Falisa; Rahmah, Mutia Aulia; Rahma, Nabila Faza (YASIN, 2025)
Social anxiety disorder is one of the most common yet frequently undetected psychological conditions, characterized by intense and irrational fear of social situations that can hinder an individual’s productivity and relationships. Emotional Freedom Technique (EFT) has emerged as a fast and non-invasive alternative therapeutic approach to reduce anxiety symptoms and is increasingly applied in counseling practice. This study aims to analyze scientific literature trends on the use of EFT in addressing social anxiety through a bibliometric approach. Data were sourced from the Scopus and Google Scholar databases within the 2010–2025 period and analyzed using Publish or Perish and VOSviewer software. The analysis results show a significant increase in publications related to EFT, particularly since 2018, with the highest research concentration originating from developed countries such as the United States, the United Kingdom, and Australia. These findings indicate growing academic interest in EFT as a psychological intervention. Although many studies support the effectiveness of EFT, further research with more rigorous methodological designs is needed to ensure validity and replicability. This study offers an initial contribution to the scientific mapping of EFT and can serve as a reference for researchers and counseling practitioners to consider EFT as a potential therapeutic technique for addressing social anxiety.